Correlation Between Fibrosis-4 (FIB-4) Score and Metavir Score of Chronic Hepatitis C (CHC) Patients in Saiful Anwar Hospital Malang - Ekamaya Sofa Irawati; Bogi Pratomo (The Indonesian Society for Digestive Endoscopy, 2019)
Background: Hepatitis C still remain a serious problem in Indonesia lead to increasing prevalence , major morbidity and mortality. Liver biopsy is gold standar, invasive procedure for liver fibrosis staging for treatment monitoring and fibrosis regression. Fibrosis-4 (FIB-4) score has been proposed as a non-invasive, easy, inexpensive as alternative indirect marker for the assessment of liver fibrosis in chronic hepatitis C (CHC).Method: Analytical cross sectional study was conducted among 54 patients with CHC from 2012 -2017 in Saiful Anwar Hospital Malang. Subjects were examined for complete blood count, aspartate aminotransferase (AST), alanine aminotransferase (ALT), anti hepatitis C virus (anti HCV), hepatitis C virus ribonucleic acid (HCV RNA), genotype, and performed liver biopsy. Statistical analysis was performed using Spearman test and statistical significant was assumed when p 0,05.Results: Fifty four (54) patients were fulfilled the selection criteria from total 67 patients. 29 (53%) males, and 25 (47%) were females. The characteristic were 33 (61%) genotype 1, 12 (22%) genotype 2, 5 (9%) genotype 3, and undetermined 3 (6%); with means of HCV RNA titer 2,57 x 106, AST 79 ± 44 IU/L, ALT 77 ± 48 IU/L platelet 160.000/mm3. Distribution of Metavir F1 10 (19%) , Metavir F2 31(57%), Metavir F3 6(11%), and Metavir F4 7 (13%). Median of FIB-4 score as Metavir F1 1,88;Metavir F2 3,24; Metavir F3 5,36; Metavir F4 4,36. There was positive correlation between FIB-4 score and Metavir score (r = 0.38; p = 0,01).Conclusion: This study indicate that there was significant correlation between FIB-4 score and Metavir score in CHC patients.